Multiple familial trichoepithelioma with malignant transformation - Rehab M Samaka; Ola A Bakry; Iman Seleit; Moshira M Abdelwahed; Rania A Hassan (Wolters Kluwer Medknow Publications, 2013)
Trichoepithelioma (TE) is a benign tumor of follicular origin that presents as small, skin-colored papules predominantly on the face. When more than one family member is affected, the disease is known as multiple familial trichoepithelioma (MFT). It is a rare autosomal dominant (AD) skin disease. Malignant transformation is very rare. We present a case of MFT in a female patient and her father with malignant transformation to basal cell carcinoma (BCC) in the father. We summarized the main histological differential parameters between TE and BCC and applied immunophenotyping for both by administration of Bcl2, CD34, CD10 and androgen receptor (AR) antibodies.